PERLINDUNGAN HUKUM TERHADAP PEMEGANG HAK CIPTA PADA PEMUTARAN FILM DI MOVIE BOX KOTA PEKANBARU - Riza Andriani; Evi Deliana; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The film is a cinematographic copyrighted work and is protected in Article 40 paragraph (1) letter m of Law Number 28 Year 2014 concerning Copyrights, so that other parties who use the economic rights of the creation must obtain the author's permission or any copyright related to Article 9 paragraph (1) and paragraph (2) UUHC. However, in the settlement that occurs against copyright, commercial films are played without the permission of the creator or copyright holder.The purpose of this study is to explain how the legal protection of copyright for films conducted by the film box business and to explain the legal remedies related to efforts to overcome copyright watching movies. Based on the results of the study referred to as copyright for films that get automatic protection from films made based on the agreement made by the creator or copyright holder of the film, they report about their copyrighted work for the Police Investigator and the IPN IPR Ministry of Justice and Human Rights. Efforts made by PPNS HKI Ministry of Law and Human Rights of the Riau Regional Office in an effort to minimize film copyrights are to make internal and external efforts, other than that what can be done by the creator or the copyright holder of the film for the copyrighted works can be done by litigation. With a lawsuit through the court can also be done by non-litigation namely through alternative dispute resolution.Releasing the Ministry of Law and Human Rights of the Riau Regional Office to deal with and minimize the violation of the copyright of the film that is happening now is increasing public awareness about UUHC law by conducting socialization to the entire community. Keywords: Film - Copyright Holder - Media Box - Commercial